Thermophysical properties of quarry dust suspension and aluminum oxide suspension as cutting fluid for machining - Liew, Pay Jun; Kursus Othman, Maisarah; Chang, Siang Yee; Wang, J.; Yap, C.Y. (Penerbit UTeM Press, 2022)
Particle additive based cutting fluid that have outstanding thermophysical properties play an essential role to reduce the cutting temperature in the machining process. In this study, thermophysical properties, namely thermal conductivity and viscosity of quarry dust suspension and aluminum oxide suspension were investigated experimentally. Both suspensions were prepared by dispersing quarry dust and aluminum oxide particles into the deionized water at various concentrations ranging from 0 wt% until 0.10 wt%. The results indicated that the thermal conductivity and viscosity were improved with the increasing concentration of both quarry dust and aluminum oxide suspension. By using 0.06 wt% of quarry dust suspension, thermal conductivity showed an improvement by 5.39% as compared to aluminum oxide suspension at the same concentration. However, higher viscosity can be obtained by using aluminum oxide suspension. This study provides insights into the thermophysical properties of quarry dust and aluminum oxide suspension, which could be beneficial to the machining industries.